Advances in Ergonomics in Design Proceedings of the AHFE 2017 International Conference on Ergonomics in Design, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA - Rebelo, Francisco; Soares, Marcelo (Advances in Intelligent Systems and Computing, 2018)
This book provides readers with a timely snapshot of ergonomics research and methods applied to the design, development and prototyping - as well as the evaluation, training and manufacturing - of products, systems and services. Combining theoretical contributions, case studies, and reports on technical interventions, it covers a wide range of topics in ergonomic design including: ecological design; educational and game design; cultural and ethical aspects in design; user research and human-computer interaction in design; as well as design for accessibility and extreme environments, and many others. The book places special emphasis on new technologies such as virtual reality, state-of-the-art methodologies in information design, and human-computer interfaces. Based on the AHFE 2017 International Conference on Ergonomics in Design, held on July 17-21, 2017, in Los Angeles, California, USA, the book offers a timely guide for both researchers and design practitioners, including industrialdesigners, human-computer interaction and user experience researchers, production engineers and applied psychologists.